KURIKULUM MERDEKA VS PENDEKATAN DEEP LEARNING : KESEIMBANGAN TEKNOLOGI DIGITAL DENGAN PENDEKATAN PENDAGOGIS - Praditya, Giceila Dias; Triana, Dinny Devi; Safrina, Rien (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
The advancement of digital technology has driven a paradigm shift in the field of education, including in the implementation of the Merdeka Curriculum, which grants teachers the flexibility to design learning experiences independently and creatively. However, in practice, music education at the junior high school level still faces challenges, such as the limited availability of digital teaching materials that align with transformative pedagogical principles. This study aims to explore and compare the integration of digital technology and pedagogical approaches within the Merdeka Curriculum and the Deep Learning Approach, particularly in the context of developing digital music learning materials. A descriptive qualitative method was employed, using data collection techniques such as semi-structured interviews, classroom observations, and document analysis. The research subjects consisted of junior high school music teachers from two schools implementing different curricula. The findings indicate that teachers who adopted the Deep Learning Approach felt more supported in developing constructive, reflective, and contextual learning due to the presence of explicit guidance in the teaching materials. In contrast, teachers using the Merdeka Curriculum enjoyed greater flexibility but still struggled to design project-based learning and integrate technology due to the lack of systematic guidance. The study concludes that the Deep Learning Approach is more effective in addressing the challenges of integrating digital technology with deep pedagogical approaches. It can serve as a meaningful and applicable alternative for developing digital music teaching materials at the junior high school level. ABSTRAKPerkembangan teknologi digital telah mendorong perubahan paradigma dalam dunia pendidikan, termasuk dalam implementasi Kurikulum Merdeka yang memberi keleluasaan bagi guru untuk mendesain pembelajaran secara mandiri dan kreatif. Namun, dalam praktiknya, pembelajaran seni musik di tingkat SMP masih menghadapi tantangan seperti keterbatasan bahan ajar digital yang sesuai dengan prinsip pedagogis transformatif. Penelitian ini bertujuan untuk mengeksplorasi dan membandingkan integrasi teknologi digital dan pendekatan pedagogis dalam Kurikulum Merdeka dan Pendekatan Deep Learning, khususnya dalam konteks pengembangan bahan ajar digital seni musik. Metode yang digunakan adalah pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa wawancara semi-terstruktur, observasi kelas, dan studi dokumentasi. Subjek penelitian terdiri dari guru-guru seni musik SMP di dua sekolah yang menerapkan kurikulum berbeda. Hasil penelitian menunjukkan bahwa guru yang menggunakan Pendekatan Deep Learning merasa lebih terbantu dalam mengembangkan pembelajaran yang konstruktif, reflektif, dan kontekstual, karena adanya panduan eksplisit dalam bahan ajar. Sementara itu, guru pengguna Kurikulum Merdeka memiliki fleksibilitas tinggi, namun masih kesulitan dalam merancang pembelajaran berbasis proyek dan integrasi teknologi karena kurangnya arahan yang sistematis. Simpulan dari penelitian ini menunjukkan bahwa Pendekatan Deep Learning lebih mampu menjawab tantangan integrasi antara teknologi digital dan pendekatan pedagogis yang mendalam, serta dapat dijadikan alternatif dalam pengembangan bahan ajar digital seni musik yang lebih bermakna dan aplikatif pada jenjang SMP.